Internal genome deletions in two distinct classes of defective interfering particles of vesicular stomatitis virus. - Perrault, J (1979)
We have characterized the genome sequences represented in two defective interfering particles derived from the heat-resistant strain of vesicular stomatitis virus by means of end-labeling and hybridization techniques. Both defective particle RNAs, which differ slightly in size, contain 5'-end sequences identical to each other and to that of the standard infectious virus genome, for at least the first approximately 55 bases. In contrast, the 3'-end sequences of these two RNAs are different. The 3'-end sequence of the smaller RNA is identical to that of the standard genome for at least the first 48 bases. The 3'-end sequence of the larger RNA is an inverted complement of its 5' end for approximately 65 bases. The bulk of the sequences in both RNAs is derived from the 3' half of the standard genome. We also show that the two defective particles differ in vitro transcription and in vivo replication properties. These results provide direct evidence for the presence of internal genome deletions in defective interfering particles of negative-stranded RNA animal viruses and demonstrate the existence of at least two distinct classes of these particles.